A content-based analysis to identify the influence of COVID-19 on sharing economy activities - Amit, Sajid; Kafy, Abdulla - Al (Spatial information research (Online), 2022)
Activities related to Sharing economy (SE) are in a vulnerable position globally due to the COVID-19 pandemic. SE businesses related to the transport and accommodation sectors are considered riskier than others, and the pandemic has only increased concerns. As such, assessing the COVID-19 pandemic’s impact on the SE is crucial. This study aims to identify the influence of COVID-19 on SE activities. Journal and news articles, blog posts, YouTube videos, and printed and televised news have been considered as data sources for this study. Using content analysis, the study showcases how SE activities are adjusting to the pandemic-induced business landscape. The study examined SE status from four stakeholders’ viewpoints—service providers (SPs), service receivers (SRs), SE firms, and regulatory bodies (RBs). The study's findings suggest that the pandemic-induced lockdown significantly impacted job sectors, increased health risk, anxiety, reduced safety, and income for SE firms. SPs, and SRs worldwide are facing tremendous difficulties operating their activities, frequently changing guidelines to support SPs by financial assistance and SRs by standard services during the COVID-19. This study will help respective authorities and government organizations to determine the appropriate strategies for SE firms to advance their services during critical situations.